Women’s Language of Mexican Female Characters Depicted in Telenovelas: An American Studies - Andri Fernanda; Nurvita Wijayanti; M Afifulloh (BASIS (Bahasa dan Sastra Inggris), 2020)
The issue about gender equality seemed in its glory in all over the world. Women might enjoy the equality and even they had a chance to promote themselves to become the future woman leaders. Not even Mexican-American women who got the impacts of the movement of gender equality. However their telenovela show told the opposite. This study aimed to examine the female characters of telenovela through the language choices. This research wanted to prove that by having telenovela as the soap opera, Mexico had their female characters to be the subaltern which showed the inferiority toward male characters. The objects of the research were two newest telenovelas aired during 2015-2019: Vis a Vis (Locked Up) and Tiempos De Guerra (Morocco: Loves in Times of War). Descriptive qualitative method was used to comprehensively analyze the language choices by female characters in those three telenovelas. The study showed that although Mexican telenovela had improved their female characters to be the stronger ones, their language choices still depicted their inferiority toward male characters.